Risk Assessment in Cholelithiasis: Is Cholecystectomy Always to be Preferred? - Mertens, Marlies C. (Springer-Verlag, 2010)
BACKGROUND: As many patients with gallstone disease do not benefit from cholecystectomy, preoperative recognition of such high-risk patients is important. The aim of the study is to identify predictors of persisting symptoms at 6 months after cholecystectomy for patients with different preoperative symptomatology. METHOD: Participants in this prospective study were consecutive patients (n = 172), age 18–65 years, with symptomatic cholelithiasis, undergoing a laparoscopic cholecystectomy. Predictors were identified using uni- and multivariate regression analyses. RESULTS: At 6 months postcholecystectomy, patients with only preoperative biliary symptoms were most often free of symptoms (62.5%). Patients with only dyspeptic symptoms most often reported persistence of preexisting symptoms (63.2%). Preoperative non-specific symptoms predicted the report of postoperative biliary and/or dyspeptic symptoms (OR = 4.5–6.1). Persistence of preexisting pattern of symptoms was predicted by the use of psychotropic medication (OR = 5.3) and dyspeptic symptoms (OR = 4.5). Postoperative biliary symptoms were predicted by High Trait Anxiety (HTA) (OR = 10.6). CONCLUSION: Surgeons should take account of individual risks of patients in the management of cholelithiasis. Instead of cholecystectomy, expectative management should be the first choice in patients with non-specific symptoms, with dyspeptic symptoms only, with HTA and in patients using psychotropic medication.